Climate warming enhances polar cod recruitment, at least transiently. (August 2017) - Bouchard, Caroline; Geoffroy, Maxime; LeBlanc, Mathieu; Majewski, Andrew; Gauthier, Stéphane; Walkusz, Wojciech; Reist, James D.; Fortier, Louis
Graphical abstract: Highlights: Early ice breakup and warm spring SST increase biomass of age-0 polar cod in fall. In warm years, improved recruitment results from higher survival of early hatchers. Observed trends in ice breakup should increase polar cod biomass in the short term. In the longer term, polar cod will likely be replaced by boreal forage fish. Abstract: Polar cod ( Boreogadus saida ) is the dominant forage fish in Arctic seas and the main prey of the ringed seal ( Pusa hispida ), the beluga ( Delphinapterus leucas ) and several seabird species. Changes in the abundance of polar cod will have cascading effects on arctic marine ecosystems. We tested the hypothesis that an earlier sea ice breakup and warmer sea surface temperatures (SST) in spring-summer result in the higher recruitment of juvenile polar cod in late summer. The density (number m −2 ) and biomass (mg m −2 ) of age-0 polar cod in August and September, estimated by hydroacoustics over 9 years in 9 areas of the Canadian Arctic, were negatively correlated to ice breakup week and positively correlated to SST. The timing of the ice breakup was the main determinant of recruitment, with mean juvenile biomass in September up to 11 times greater for early breakup (late May) than for late breakup (early September). Early ice breakup in spring increased juvenile biomass in August and September by allowing the survival of larvae hatched in winter and spring. Since 1979, ice breakup has occurred earlier by as much as 9.3 days per decade in some areas. We thus forecast a transient increase in polar cod biomass over the first part of the present century. Thereafter, the relaxation of extreme climatic conditions in Arctic seas should harbinger the replacement of the hyper-specialized polar cod by subarctic and boreal forage fish.